STRATEGI GURU DALAM MENANAMKAN NILAI-NILAI DISIPLIN PADA PESERTA DIDIK SMA MUHAMMADIYAH - Ridho Hidayah; Nia Asmara; Nur Azizah; Pipin Danu Marti (Smart Education, 2026)
Abstract: This study aims to analyze teachers’ strategies in instilling discipline values among students at Muhammadiyah Senior High School. Discipline is considered an essential character value that supports students’ academic achievement and moral development. This research employed a qualitative descriptive approach to obtain an in-depth understanding of how teachers implement discipline-oriented strategies in the school environment. The research subjects included subject teachers, Islamic education teachers, and school staff who play a role in fostering student discipline. Data were collected through in-depth interviews, observations, and documentation. The collected data were analyzed using data reduction, data display, and conclusion drawing techniques, while data validity was ensured through source and technique triangulation. The findings reveal that teachers apply various strategies to instill discipline values, including role modeling, habituation through school rules, effective classroom management, and the integration of discipline values into the learning process. Teachers consistently demonstrate disciplined behavior, such as punctuality and responsibility, which positively influences students’ attitudes. In addition, the implementation of clear and consistent school regulations helps students develop disciplined habits in their daily activities. The integration of technology-based learning also supports discipline by training students to manage time, complete assignments responsibly, and use digital media ethically. Furthermore, the application of educational reward and punishment strengthens students’ motivation and awareness of discipline. Overall, teachers’ strategies have proven effective in fostering students’ discipline and character development. This study concludes that teachers play a crucial role in shaping students’ discipline through comprehensive, consistent, and value-based educational practices. Keyword: Discipline Values; Teacher Strategies; Character Education Abstrak: Penelitian ini bertujuan untuk menganalisis strategi guru dalam menanamkan nilai-nilai disiplin di kalangan siswa SMA Muhammadiyah. Disiplin dianggap sebagai nilai karakter penting yang mendukung prestasi akademik dan perkembangan moral siswa. Penelitian ini menggunakan pendekatan deskriptif kualitatif untuk memperoleh pemahaman mendalam tentang bagaimana guru menerapkan strategi berorientasi disiplin di lingkungan sekolah. Subjek penelitian meliputi guru mata pelajaran, guru pendidikan agama Islam, dan staf sekolah yang berperan dalam membina kedisiplinan siswa. Data dikumpulkan melalui wawancara mendalam, observasi, dan dokumentasi. Data yang dikumpulkan dianalisis menggunakan teknik reduksi data, penyajian data, dan penarikan kesimpulan, sedangkan validitas data dipastikan melalui triangulasi sumber dan teknik. Hasil penelitian menunjukkan bahwa guru menerapkan berbagai strategi untuk menanamkan nilai-nilai disiplin, termasuk teladan, pembiasaan melalui peraturan sekolah, manajemen kelas yang efektif, dan integrasi nilai-nilai disiplin ke dalam proses pembelajaran. Guru secara konsisten menunjukkan perilaku disiplin, seperti ketepatan waktu dan tanggung jawab, yang secara positif memengaruhi sikap siswa. Selain itu, penerapan peraturan sekolah yang jelas dan konsisten membantu siswa mengembangkan kebiasaan disiplin dalam kegiatan sehari-hari mereka. Integrasi pembelajaran berbasis teknologi juga mendukung disiplin dengan melatih siswa untuk mengatur waktu, menyelesaikan tugas secara bertanggung jawab, dan menggunakan media digital secara etis. Lebih lanjut, penerapan penghargaan dan hukuman pendidikan memperkuat motivasi dan kesadaran siswa akan disiplin. Secara keseluruhan, strategi guru telah terbukti efektif dalam menumbuhkan disiplin dan pengembangan karakter siswa. Studi ini menyimpulkan bahwa guru memainkan peran penting dalam membentuk disiplin siswa melalui praktik pendidikan yang komprehensif, konsisten, dan berbasis nilai. Kata kunci: Nilai Disiplin; Strategi Guru; Pendidikan Karakter